Leveraging the DIFFIT App for Culturally Integrated Language Teaching in Elementary Education - Unun, Veronika; Nugrahani, Farida; Widayati, Mukti; Juidah, Imas; Widyaningrum, Heny Kusuma; Sohnui, Suhailee (IJORER : International Journal of Recent Educational Research, 2025)
This study examines the use of the Diffit app to improve language training and preserve local cultural values, notably wayang (traditional Javanese puppetry), at State Elementary School Jombor 1 in Bendosari, Sukoharjo, Central Java. The data were collected using a descriptive qualitative method with an embedded case study design through classroom observations, interviews with teachers and students, and supplementary documentation. The study showed that tailored training greatly enhanced teachers’ proficiency in using Diffit, with measurable increases in comprehension and digital teaching skills. Prior to training, most teachers displayed basic comprehension; after training, many attained high mastery levels, with some improving by 100%. This shows the importance of structured digital training in improving teachers’ technological and pedagogical competencies. In addition to improving language training, Diffit was useful in introducing and strengthening local cultural elements. Teachers found increased creativity and student engagement when using the app to access wayang-related books, while students showed better interest in and understanding of traditional culture through digital media. These results show how culturally relevant digital tools can connect traditional content and new learning environments. The findings are consistent with previous studies on the benefits of digital tools in education, particularly in circumstances needing both instructional efficacy and cultural preservation. This study emphasises Diffit’s dual function as a language teaching aid and a medium for sustaining local tradition, indicating its broader usefulness in culturally sensitive, tech-enhanced elementary education.